2011
DOI: 10.1080/10934529.2011.598788
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical characteristics of Kuan-Tzu-Ling, Chung-Lun and Bao-Lai hot springs in southern Taiwan

Abstract: Hot springs are the important natural sources of geothermally heated groundwater from the Earth's crust. Kuan-Tzu-Ling (KTL), Chung-Lun (CL) and Bao-Lai (BL) are well-known hot springs in southern Taiwan. Fluid and mud (sediments) samples were collected from the eruption points of three hot springs for detailed biogeochemical characterization. The fluid sample displays relatively high concentrations of Na(+) and Cl(-) compared with K(+), Mg(2+), Ca(2+), NO(2) (-), and SO(4) (2-), suggesting a possible marine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Desulfovibrio psychrotolerans-related strains were also isolated from similar sites, e.g., from the Chung-Lun hot spring (southern Taiwan; Maity et al 2011). D. psychrotolerans-related sequences were retrieved from the volcanic lake Kauhako (Donachie et al 2004), from the Chung-Lun hot spring (southern Taiwan; Maity et al 2011), and from an oil field microbial community ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Desulfovibrio psychrotolerans-related strains were also isolated from similar sites, e.g., from the Chung-Lun hot spring (southern Taiwan; Maity et al 2011). D. psychrotolerans-related sequences were retrieved from the volcanic lake Kauhako (Donachie et al 2004), from the Chung-Lun hot spring (southern Taiwan; Maity et al 2011), and from an oil field microbial community ).…”
Section: Resultsmentioning
confidence: 99%
“…D. psychrotolerans-related sequences were retrieved from the volcanic lake Kauhako (Donachie et al 2004), from the Chung-Lun hot spring (southern Taiwan; Maity et al 2011), and from an oil field microbial community ). This may be indicative for a broad ecological amplitude, at least with respect to environmental temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated As levels in groundwater were found in two neighboring catchments including the Chianan Plain and the southern Choushui River alluvial fan in Taiwan [21,67,137,162,176]. The reduction potential in the Chianan Plain is stronger than that of the Choushui River alluvial fan, and the difference in reduction potentials between these two vicinal areas is believed to be the cause of the exceptional concentrations of As in groundwaters [177,178].…”
Section: Taiwanmentioning
confidence: 99%
“…Countries of particular concern in this region include Bangladesh, West Bengal (India), China, Vietnam, Taiwan, Thailand, and Nepal because of widespread problems associated with As within their populations [1,13,137,138]. Arsenic found in the Ganges-Meghna-Brahmaputra basin in southern Asia is an important example of natural contamination.…”
Section: Southeast Asiamentioning
confidence: 99%
“…Analyses of expelled fluids in our pilot surveys (unpublished data) and previous studies ( 88 , 89 ) revealed a markedly large sulfate content (up to 2 mM) and reducing state (−400 to −100 mV), a physiochemical condition favorable for the proliferation of sulfate reducers. The recorded temperature of fluid ranged between 40°C and 90°C ( 10 , 54 ), suggesting that fluids originating at depth likely mixed with low-temperature groundwater prior to being discharged to the surface environments. As a consequence, microorganisms from the deep biosphere have to cope with dynamic temperature variations during fluid transport, and compete with populations introduced from a shallower subsurface for substrate availability.…”
mentioning
confidence: 99%